The Effect of IP Constituent Position and Foot Complexity on Timing in Polish Learner's English Pronunciation - Porzuczek, Andrzej (Research in Language, 2010)
This paper focuses on the effect of prominence level and stress distribution on timing in read English speech of Polish learners. We have measured and analysed the length of IP units distinguished by the traditional British School prosodic description, i.e. preheads, heads and nuclei, as well as stress feet, further divided into stressed and unstressed syllables. A comparison of native and Polish learners' performance shows similar durations of stressed and pitch accented syllables. The unstressed syllables and syllable clusters, on the other hand, are significantly longer in non-native speech, and the discrepancies increase at lower phrasal prominence levels, especially in the preheads. Similar results for both groups have been obtained with respect to the number of consecutive unstressed syllables (foot complexity). The same test repeated after seven months of pronunciation training reveals a considerable tendency towards native speech timing, although the differences concerning low prominence levels remain significant.